Semantic Structures of Unique Verbs in Souret Al-Baqarah - Al-Maaytah, Khaled Salman Obaid (Journal of Arabic Language Sciences and Literature, 2022)
The research addresses the unique verbs e in Surat Al-Baqarah, which were not mentioned except in this surah, so the study was conducted on the construction of the verb and lexically, morphologically and semantically following it pating attention to its occurrence in the contexts of the Qur’anic verse, and attempting to reveal the ambiguity of the verbs’ use as it is in derivatives, and clarifying the morphological construct by Which it has come where a number of changes occurred in it such as reversing, deletion and substitution, and this is undoubtedly one of the secrets of the Arabic language, which is characterized by flexibility and consistency of verbs with its appropriate meaning and temporal and interactive significance in light of the unique Qur’anic structure for each verbs.